2020
DOI: 10.1136/thoraxjnl-2019-214355
|View full text |Cite
|
Sign up to set email alerts
|

Mucoactive agents for acute respiratory failure in the critically ill: a systematic review and meta-analysis

Abstract: PurposeAcute respiratory failure (ARF) is a common cause of admission to intensive care units (ICUs). Mucoactive agents are medications that promote mucus clearance and are frequently administered in patients with ARF, despite a lack of evidence to underpin clinical decision making. The aim of this systematic review was to determine if the use of mucoactive agents in patients with ARF improves clinical outcomes.MethodsWe searched electronic and grey literature (January 2020). Two reviewers independently screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…This rationale is echoed in a recent study exploring UK physiotherapy practice (Connolly et al., 2020 ). Despite high use, a recent systematic review and meta‐analysis does not support the use of mucoactive agents in critically ill patients with acute respiratory failure, however it is noted the existing evidence base is of low quality (Anand et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…This rationale is echoed in a recent study exploring UK physiotherapy practice (Connolly et al., 2020 ). Despite high use, a recent systematic review and meta‐analysis does not support the use of mucoactive agents in critically ill patients with acute respiratory failure, however it is noted the existing evidence base is of low quality (Anand et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Data from meta- analysis of 4 mucoactive agents (including NAC, hypertonic saline, heparin, and ambroxol) across 13 randomized control trials have shown no effect on the duration of mechanical ventilation or hospital stay, but the analysis demonstrated a small effect on reducing ICU length of stay in the mucoactive agent groups (10 trials, 95% CI −5.49 to -0.96, I 2 = 89%) was appreciated ( Anand et al, 2020 ).…”
Section: Therapies Addressing Underlying Mucus Alterationsmentioning
confidence: 99%
“…(8) In mechanically ventilated patients, nebulized N-acetylcysteine was not more effective than normal saline nebulization in reducing the secretion thickness. (9) A recent meta-analysis (10) described four mucoactive agents (N-acetylcysteine, ambroxol, hypertonic saline, and heparin) showed that mucoactive agents did not affect the duration of mechanical ventilation or mortality, hospital stay, and ventilator-free days, but only reduced the length of stay at ICU with a very low certainty. Thus, high-quality, randomized, controlled trials are needed to determine the efficacy of inhaled mucus-regulating agents in critically ill patients.…”
Section: High Popularity Of Inhaled Mucus-regulating Agentsmentioning
confidence: 99%